An ultrasound-assisted green synthesis of 1,3-diphenyl pyrazole-based spirooxindolo-1,2,4-oxadiazoles: their in vitro anti-tubercular activity and in silico molecular dynamics - Baddepuri, Sravanthi; Gamidi, Rama Krishna; Kumari, Jyothi; Sriram, Dharmarajan; Gangarapu, Kiran; Basavoju, Srinivas (Chemistryselect, 2025)
A simple base-mediated one-pot synthetic green methodology has been successfully employed for the synthesis of 1,3-diphenylpyrazole-based spirooxindolo-1,2,4-oxadiazole derivatives. The newly synthesized analogues were tested for their in vitro anti-tubercular activity (anti-TB) against Mycobacterium tuberculosis H37Rv strain, and the results were reported as minimum inhibitory concentration (MIC) values ranging from 3.125 to 25 mu g/mL. Especially, the five compounds 3a, 3f, 3k, 3q, and 3v exhibited good to moderate anti-TB activity with MIC of 3.125 mu g/mL when compared to the reference drug ethambutol (MIC: 1.56 mu g/mL). In silico Molecular docking and molecular dynamics simulations of the protein-ligand complex (3a, 3f, 3k, and 3v) against Mycobacterium tuberculosis DprE1 (PDB ID: 5OEQ) of M. tuberculosis H37Rv strain revealed that these four compounds could be promising anti-mycobacterial candidates, as evident from the binding results and stability of the docked-ligand complexes with considerable least binding energies. ADME parameters were also studied to assess the drug likeness, which clearly shows that the newly developed compounds might be useful for the future development of novel anti-tubercular drugs.
Keywords: 1; 2; 4-oxadiazoles; In silico molecular dynamic studies; In vitro anti-tubercular activity; ultrasonication